1970
DOI: 10.3329/jbau.v6i2.4826
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and pathology of <i>Trichomonas gallinae</i> in the common pigeon (<i>Columba livia</i>)

Abstract: Pigeons (n=300) were examined during July 2007 to June 2008 in different areas of Mymensingh district. Of the pigeons examined, 202 (67.3%) were infected by Trichomonas gallinae (Rivolta, 1878). Prevalence of Trichomonas gallinae was higher in female pigeon (70.9%) than male pigeon (63.8%). Adult pigeons aged >3 months were comparatively more affected (75%) than the squab aged <30 days (72.1%) and the younger aged between 30 days to 90 days (64.7%). T. gallinae infection was significantly (P<0.01) lower in sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 7 publications
5
15
1
Order By: Relevance
“…During this study (June 2010) 65.7 % pigeons were infected with T. gallinae which supported the findings of Begum et al (2008), De Carli et al (1979) and McKeont et al (1997), who recorded 67.3, 62.3 and 59.0 % prevalence of T. gallinae in pigeons in Bangladesh, Brazil and Australia, respectively (Begum et al 2008;De Carli et al 1979;McKeon et al 1997). But, the present finding is found higher prevalent rate than that of Villanua et al (2006), Tasca and De Carli (1999) and Toro et al (1999), who reported 34.2, 26.5 and 11 % T. gallinae infection in pigeon in Spain, Brazil and Chile, respectively (Tasca and De Carli 1999;Toro et al 1999;Villanua et al 2006).…”
Section: Discussionsupporting
confidence: 90%
“…During this study (June 2010) 65.7 % pigeons were infected with T. gallinae which supported the findings of Begum et al (2008), De Carli et al (1979) and McKeont et al (1997), who recorded 67.3, 62.3 and 59.0 % prevalence of T. gallinae in pigeons in Bangladesh, Brazil and Australia, respectively (Begum et al 2008;De Carli et al 1979;McKeon et al 1997). But, the present finding is found higher prevalent rate than that of Villanua et al (2006), Tasca and De Carli (1999) and Toro et al (1999), who reported 34.2, 26.5 and 11 % T. gallinae infection in pigeon in Spain, Brazil and Chile, respectively (Tasca and De Carli 1999;Toro et al 1999;Villanua et al 2006).…”
Section: Discussionsupporting
confidence: 90%
“…The values found in the present study of helminth infestation were significantly higher than those of helminth infestation of pigeon observed by Radfar et al (2011) and Natala et al (2009). So far, information on the helminth parasites of Columba livia is scanty in Bangladesh, except that of Begum et al (2008) who observed epidemiology and pathology of protozoan parasites in Trichomonas gallinae in the common pigeon (Columba livia). The present study thus provides baseline or preliminary information on the subject.…”
Section: Resultsmentioning
confidence: 99%
“…Several health issues will have an effect on pigeons; however, parasitic infections will play an important role. The role of pigeons in the transmission of disease to other pigeons, domestic animal, and poultry and especially to human has been well documented by many authors [2,3].…”
Section: Introductionmentioning
confidence: 99%